2018
DOI: 10.1142/s2010135x18500145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sintering temperature on microstructure and nonlinear electrical characteristics of ZnO varistor

Abstract: The nonlinear properties of ZBMCCS-based varistors, which are composed of ZnO–Bi2O3–MnO2–Cr2O3–Sb2O3–Co3O4 and SiO2 are studied inrelation to sintering temperature, in the range of 1280–1350[Formula: see text]C. The samples are investigated for grain morphology by using scanning electron microscope (SEM). These samples were examined by using X-ray diffraction patterns (XRD) and DC electrical measurements. X-ray diffraction analysis of the samples show the presence of ZnO, Zn2SiO4 willemite phase and Co[Formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…The radial homogeneity and the electrical stability after being exposed to the atmosphere for the sample C are illustrated in Figure S2 and S3 (Supporting Infromation), and the electrical parameters are summarized in Table S1 and S2 (Supporting Information). Compared with high-breakdown ZnO varistor ceramics fabricated by conventional thermal sintering process (TSP) [30][31][32], microwave sintering (MWS) [6], two-step sintering (TSS) [33], microwave two-step sintering (MW-TSS) [34] and spark plasma sintering (SPS) [35], cold sintered samples show a combination of good nonlinear coefficient and superior breakdown electric field together with an extreme low sintering temperature, as listed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The radial homogeneity and the electrical stability after being exposed to the atmosphere for the sample C are illustrated in Figure S2 and S3 (Supporting Infromation), and the electrical parameters are summarized in Table S1 and S2 (Supporting Information). Compared with high-breakdown ZnO varistor ceramics fabricated by conventional thermal sintering process (TSP) [30][31][32], microwave sintering (MWS) [6], two-step sintering (TSS) [33], microwave two-step sintering (MW-TSS) [34] and spark plasma sintering (SPS) [35], cold sintered samples show a combination of good nonlinear coefficient and superior breakdown electric field together with an extreme low sintering temperature, as listed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work (Bouchekhlal and Hobar, 2018), we have studied the electrical properties of ZBMCCS-based varistors for various sintering temperatures. We have reported that this system gives a relatively high nonlinearity coefficient α = 33.61, low leakage current of 210 µA/cm 2 at sintering temperature of 1280°C.…”
Section: Resultsmentioning
confidence: 99%
“…As far as our present work is concerned, we studied the effects of the sintering temperature on the ZnO-based varistors with small additions of bismuth, manganese, chrome, antimony and cobalt oxides (ZBMCSC). Also, this paper is considered as the continuation of the previous works in the grain growth of ZBMCCSS varistors (Bouchekhlal and Hobar, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…The microstructure of the ZnO varistors was investigated via scanning electron microscopy (SEM) (model: JSM -6460 LV). The average grain size (D) was estimated with the linear intercept technique [4][5][6].…”
Section: Characterizationmentioning
confidence: 99%